Analisis Cognitive Bias pada Perilaku Pengambilan Keputusan Manajer Investasi: Studi pada Perdagangan Emas Online di PT Valbury Asia Futures Cabang Yogyakarta - Virgilio Cancera Meliala; Waspada Meliala (Jurnal Publikasi Ilmu Manajemen, 2024)
This study aims to analyze the cognitive bias behavior of investment managers by analyzing behavioral finance which is characterized by sometimes rational and irrational decision making so that it has an impact on investor confidence in investment managers in terms of analyzing online gold trading at PT Valbury Asia Futures Yogyakarta Branch. This type of research the writer uses descriptive qualitative method using primary data as a reference obtained from observations and interviews with investment managers. Primary data is a collection of information that can be processed from research sources whose data is obtained directly from the original source. The sample or respondents in this study were 4 investment managers who led the marketing division. The variable studied, namely Behavioral finance, leads to the irrational behavior of investment managers towards their decision making. This behavior can be of various kinds, such as: heuristic, overconfidence, mental accounting, framing, representative, conservative and disposition effects. Based on the results of the analysis on the financial behavior of managers, there are factors that cause their behavior to be irrational by using personal opinions, excessive self-confidence, selfishness, the nature of the gambling method, individualism, and hasty in making transaction conclusions.